Asas Equality Before the Law: Perspektif Historis dan Penerapannya di Indonesia - Karmin (Policy and Law Journal, 2024)
The principle of equality before the law is a fundamental principle in the legal system that guarantees that every individual has equal standing before the law without discrimination. This research aims to examine the historical, theoretical, and implementation aspects of this principle in Indonesia, as well as identify the main challenges in its application. This research uses a normative legal method with a historical approach and a statutory approach. Data was collected through a literature study, including analysis of primary legal documents such as laws and court decisions, as well as secondary sources such as scholarly articles and other legal literature. The results show that although the principle of equality before the law has been embedded in the constitution and various national regulations, its implementation still faces various obstacles. The main obstacles include inconsistencies in law enforcement, the influence of power in the judicial system, and limited access to justice for vulnerable groups. As a recommendation, stricter legal reforms, increased transparency in the justice system, and legal education to the public are needed to ensure that the principle of equality before the law can be applied effectively and fairly in Indonesia.